PENGARUH MODEL PEMBELAJARAN COURSE REVIEW HORAY TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS XI IIS SMA NURUL FALAH PEKANBARU - Cynthia Rahmi; Sri Kartikowati; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aims to find out the effect of course review horay learning model on student learning achievement. This research used quasy experimental method and involve student class XI IIS 1 as experimental class and student class XI IIS 2 as control class. Data retrieval process start from pretest in two class and give treatment in experimental class. Data analysis techniques used are Homogenity test, normality test, paired sample t- test and N-Gain Test with the help of SPSS version 19.0 and calculation with formula manually. The result of this research are there is a significant different in economic learning achievement between two class. The average of learning achievement in experimental class is 76,72 and for control class is 71,20. The teacher activity in class is includ in perfect category with score in meeting I, II, and III : 53, 58 and 60. The student activity include in good activity category with score meeting I, II, and III : 30, 33 and 32. Course Review Horay learning model has significant effect for student learning achievement of 0,81. This research show that the Course Review Horay model learning has a positive effect to economic learning achievement. This means that student-centered learning models can improve student learning activities and have a positive effect on student learning achievements. To improve student learning achievement the support of the teacher is needed in the form of an effective learning model.Keyword:Cooperative Learning, Course Review Horay, Learning Achievement